Analysis of activated clotting time in patients receiving unfractionated heparin with and without continuous infusion during elective percutaneous coronary intervention - Saidi, Zaki; Widito, Sasmojo (Universitas Brawijaya, 2025)
Background: Percutaneous coronary intervention (PCI) involves a risk of thrombotic events. Unfractionated heparin (UFH) remains a preferred antithrombotic agent during PCI, though the optimal administration method is still under debate. Given its narrow therapeutic range, UFH requires careful monitoring through the measurement of activated clotting time (ACT) Objective: The aim is to compare ACT value and the outcomes of administering a bolus of UFH at 70–100 IU/kgBW, with and without a continuous infusion of 2000 IU/hour Methods: An observational retrospective study was conducted on 133 patients who underwent elective PCI by meeting the inclusion and exclusion criteria during the period of July 2022–July 2024. Clinical information, ACT value and the outcome were gathered from medical records. Statistical analyses were performed using SPSS 22, employing univariate, bivariate, and multivariate logistic regression analyses to determine correlations. Result: The range of ACT results of administering an UFH bolus of 70-100 IU/kgBW with continuous infusion 2000 IU/hour was 191 to 426 seconds (mean 281.9 seconds). Among the 44 patients, 66.6% exhibited ACT levels below 300 seconds, 15 patients (22.7%) had ACT levels ranging from 300 to 350 seconds, while 6 patients (8.3%) had ACT levels exceeding this range. The percentage of patients who attained therapeutic success in the unfractionated heparin (UFH) infusion group (22.7%) was significantly higher than the UFH bolus group (5.9%) with statistically significant results (p = 0.000). Complications were observed in both groups, with 1 patient in each group experiencing acute thrombosis (p = 1.000) and no patients experienced bleeding complications. Conclusion: Administering a UFH bolus of 70-100 IU/kgBW with continuous UFH infusion at 2000 IU/hour achieved better optimal ACT values. No significant results were found regarding the risk of acute thrombosis with no bleeding complications.